Literacy and language teaching - Kern, Richard (Oxford University Press, 2000)
This book discusses the need for foreign language programmes to teach literacy. It suggests approaches to curriculum development using a wide range of modern media texts such as newspapers, music videos, and film as a basis for cultural analysis